Saudi Arabia : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2016)
This Selected Issues paper discusses the options for financing the government fiscal deficit in Saudi Arabia. The Saudi government is working to develop a comprehensive strategy to meet its budget financing needs. Although external borrowing could alleviate pressure on the domestic market, it will also create new risks. Reliance on foreign investors may help further enhance transparency. Foreign investors' demand for diversification could also allow the Saudi government to enjoy attractive yields. Broadening the investor base and ensuring that the government's debt issuance supports the development of the private debt market could help alleviate some of the negative economic and financial effects of higher government debt.